WAYS OF DEVELOPING METHODOLOGICAL COMPETENCE OF FUTURE FINE ARTS TEACHERS - Shovdirov Sunnat Aslanovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the content, importance, and effective ways of developing methodological competence among future fine arts teachers. Methodological competence is a key component of a teacher’s professional activity, enabling the integration of theoretical knowledge with practice, the use of modern pedagogical technologies, and the fostering of students’ aesthetic taste and creativity. The paper analyzes the role of innovative approaches, interactive methods, and practical training in enhancing methodological competence.